PENGGUNAAN PENDEKATAN STEAM BERBAHAN LOOSE PARTS UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK KELAS B DI RA AL-AKBAR TANJUNG MORAWA - Dwi Andria Ningsih; Juli Maini Sitepu (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This research was motivated by the fact that the learning process carried out using the STEAM approach made from Loose Parts was not optimal, the word Loose Parts was not yet familiar, learning activities were teacher-centred and children's thinking abilities were not optimal. The aim of this research is to determine the use of the STEAM approach made from Loose Parts to improve the cognitive aspects of class B children at RA Al-Akbar Tanjung Morawa. This type of research uses a qualitative approach with data collection techniques through observation, interviews and documentation. This data analysis technique is carried out using data reduction, data presentation and drawing conclusions. The implementation of the approach to using STEAM made from Loose Parts in improving the cognitive aspects of class B children in the scope of learning development and problem solving, logical and symbolic thinking at RA Al-Akbar Tanjung Morawa has been successfully implemented, it has been proven that children are able to think critically to solve everyday problems by using technology. From the assessment data on children's cognitive development achievements, there was an increase of 16.65%. Data before the research included 13.3% of BB children, 40.0% of MB children, 26.7% of BSH children and 20.0% of BSB children. Data after research showed that the percentage was 6.7% BB children, 13.3% MB, 40.0% BSH, 40.0% BSB.